Development and Validation of Learning Activity Sheets in Rational Expressions and Linear Equations and Inequalities - Lacea, Justine P; Buscano, Jay D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The purpose of this research study is to develop Learning Activity Sheets (LAS) in Rational Expressions and Linear Equations and Inequalities for the students. Data were collected via survey questionnaire from three sets of evaluators. The LAS was also administered from 100 students of New Society National High School to further scrutinize its validity. The results were interpreted and analysed using the rating scale and statistical tools including on-way ANOVA and mean. Based from the results of the study, the researcher concluded that: there were fourteen competencies included in the developed LAS which are the not mastered and least mastered competencies of the students. The competency that received the highest mean percentage on the competency test was LAS 17 (graphs and illustrates a linear function and its (a) domain; (b) range; (c) table of values; (d) intercepts; and (e) slope). On the other hand, the competency that received the lowest mean percentage on the competency test was LAS 12 (solves problems involving systems of linear inequalities in two variables). The evaluators found the developed LAS to be effective and useful in terms of objectives, concepts, skills, usability, appropriateness, and adequacy with an interpreted mean rating of very high extent. The researcher also concluded that there is no significant difference in the standard response of the evaluators which is composed of Grade 8 math teachers, master teachers, and LRMDS-trained teachers. Based on the mean percentage results of the administered LAS, there was also a considerable improvement in the students' learning.